1998
DOI: 10.1021/ie970212d
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Structural Characteristics of a Hydrotreatment Catalyst with Deactivation/Regeneration Cycles

Abstract: The effect of reaction/regeneration cycles on some structural characteristics of a NiMo/Al2O3 hydrotreatment catalyst has been studied. The first regeneration produces increases in pore volume, porosity, and specific area. Above 5% coke deposit, various changes in such properties appear. Mo and Ni relative XPS intensities depend on the reaction/regeneration cycles Ni exposure decreases with them, whereas Mo exposure follows the opposite trend. The effect of coke on metal dispersion seems to be almost negligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
(19 reference statements)
3
4
0
Order By: Relevance
“…The higher the percentage of sulfur in the form of the oxidation state of −2, the higher the extent of sulfidation and hence catalyst activity. The peak at the binding energy (BE) of 162.5 ± 0.2 eV indicates the formation of Ni Mo S phase or NiS [39] due to OSS of −2, which is close to the value reported in the literature [35,38,39,50,53,55]. Another peak at a higher BE (169.3) was also observed.…”
Section: Oxidation States Of Sulfursupporting
confidence: 86%
See 4 more Smart Citations
“…The higher the percentage of sulfur in the form of the oxidation state of −2, the higher the extent of sulfidation and hence catalyst activity. The peak at the binding energy (BE) of 162.5 ± 0.2 eV indicates the formation of Ni Mo S phase or NiS [39] due to OSS of −2, which is close to the value reported in the literature [35,38,39,50,53,55]. Another peak at a higher BE (169.3) was also observed.…”
Section: Oxidation States Of Sulfursupporting
confidence: 86%
“…Table 6 also shows that significant amount of oxidic Ni is still present on the catalyst surface after 30 days of run time. Brito et al [35] also reported significantly higher concentrations of oxidic Ni on the coked catalyst surface.…”
Section: Oxidation States Of Nimentioning
confidence: 92%
See 3 more Smart Citations